Identification of Workplace Accidents at PT XYZ In Sidoarjo Using The Job Safety Analysis (JSA) Method - Hakim, Luqman; Irwin, Mochammad Denis; Abdillah, Ikhwan; Masykuri, Ali (Journal of Research and Technology, 2024)
The rapid development of technology in Indonesia significantly impacts various aspects of life, including the industrial sector. One of the negative impacts on this sector is the occurrence of work accidents that cause injury and death. This is due to the low implementation of Occupational Health and Safety (K3) culture in the industrial world. PT XYZ, a company engaged in the hot rolling coil industry in Sidoarjo, implements a K3 system. However, based on initial observations, there are still obstacles, especially the lack of understanding of human resources regarding Standard Operating Procedures (SOP). This study aims to identify the factors causing work accidents and outline corrective steps to reduce the risk. Using the Job Safety Analysis (JSA) method, this study found that in 2022, there were 43 cases of work accidents, while in 2023, the number decreased to 41 cases. As a result of these accidents, in 2022, there was a loss of 21 working days per 1,000,000 working hours/person, while in 2023, the loss of working days decreased to 18 days for the same period. The accident indicator also showed a decline, from 0.47 in 2022 to 0.38 in 2023. Recommendations to prevent work accidents at PT XYZ include reading the safety board, attending briefings before work, doing work according to the job description, and using personal protective equipment such as safety shoes and work helmets.